2015
DOI: 10.1021/ic502699m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Studies, and Oxidation Catalysis of the Late-First-Row-Transition-Metal Complexes of a 2-Pyridylmethyl Pendant-Armed Ethylene Cross-Bridged Cyclam

Abstract: The first 2-pyridylmethyl pendant-armed ethylene cross-bridged cyclam ligand has been synthesized and successfully complexed to Mn(2+), Fe(2+), Co(2+), Ni(2+), Cu(2+), and Zn(2+) cations. X-ray crystal structures were obtained for all six complexes and demonstrate pentadentate binding of the ligand with the requisite cis-V configuration of the cross-bridged cyclam ring in all cases, leaving a potential labile binding site cis to the pyridine donor for interaction of the complex with oxidants and/or substrates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 66 publications
6
56
0
Order By: Relevance
“…Glyoxal-bridged cyclam-based ligands (L-R,R 0 ) have attracted much interest [1][2][3][4][5][6][7][8][9] in the last decades, due to their ability to coordinate mid-late transition metals (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glyoxal-bridged cyclam-based ligands (L-R,R 0 ) have attracted much interest [1][2][3][4][5][6][7][8][9] in the last decades, due to their ability to coordinate mid-late transition metals (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…These macrocycles can be easily N-functionalized with various groups, allowing the preparation of a wide range of ligands suitable for important applications such as for catalysis [4,8], and the development of metal-based imaging and therapeutic agents in medicine [10].…”
Section: Introductionmentioning
confidence: 99%
“…[10] [12] Analogous conditions were used for the formation of 1 . Using dichloromethane gave the desired product in relatively high yields (~80%), see Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…[8] [9] Recently we have been interested in the use of this complex type as oxidation catalysts. [10] [11] [12] A recent papers by Que, et al, has shown that addition of a pyridyl pendant arm to a tetraazamacrocycle can result in new and improved oxidation catalysis. [13] The literature contains numerous other pyridyl pendant armed tetraazamacrocycles, indicating a general interest in the community and known synthetic techniques for adding pendant pyridyl donors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation